Puritan Islam : The Geoexpansion of the Muslim World - Vann, Barry A. (Amherst, New York Prometheus Books, 2011)
In contrast to previous waves of immigrants who arrived in host countries eager to become productive and contributing members of their new homelands and desiring to adopt the native customs and culture, puritan Muslim immigrants with their more conservative, if not radical, interpretation of the dictates of Islam are likely to refuse assimilation in favor of a separatist lifestyle, seemingly cut off from the host nations. Clearly, people with a puritan Muslim mind-set are little inclined to accept a pluralistic, multicultural, live-and-let-live concept of society. And conflicts between differing value systems are almost inevitable. This author shows that this purist approach to Islam is certainly not universal among Muslims, and there are many varying interpretations that are more moderate in outlook. Nonetheless, the undeniable theological background of all Muslim communities colors their values and attitudes, and must be taken into consideration when attempting to understand the potential conflicts between contiguous Muslim and non-Muslim groups. Given the fact that the population of Muslim immigrants is growing rapidly in traditionally Christian and increasingly secular countries of the Western world while the resident populations are either stagnant or declining, Vann$1 (Bs insightful analysis of the ways in which Islam influences perceptions of community and geography is an eye-opening message of urgency and gives evidence of the social, political, and cultural changes that lie ahead.s
Include Map, Illustrations, Notes, Bibliography and Index.
The Geoexpansion of the Muslim World.
Keywords: Religion and geography -- Human geography -- Islam